Instruments for the care of pressure injury in pediatrics and hebiatrics: an integrative review of the literature - Mayara Kelly Moura Ferreira; Sabrina de Souza Gurgel; Francisca Elisângela Teixeira Lima; Maria Vera Lúcia Moreira Leitão Cardoso; Viviane Martins da Silva (Universidade de São Paulo, 2018)
ABSTRACT Objective: to identify existing instruments in the scientific literature about the care of pressure injuries in pediatric and hebiatric patients. Method: an integrative review that selected 32 articles from the PubMed/Medline, LILACS, Scopus and CINAHL databases using the descriptors pressure ulcer, decubitus ulcer, pediatrics, adolescent and protocols and their equivalent terms in Portuguese and Spanish. Inclusion criteria: research articles in full, in Portuguese, English or Spanish without any temporal cut-off. The descriptive analysis was adopted to categorize the instruments found into the three domains of care: evaluative, preventive and curative. Results: 25 instruments for the care of pressure injuries in pediatric and hebiatric patients were found, with an emphasis on the Braden Q Scale being the most commonly used to assess pressure injury risk, and the protocols containing pressure injury staging guidelines developed by the National Pressure Ulcer Advisory Panel (NPUAP) and the European Pressure Ulcer Advisory Panel (EPUAP). Conclusion: the scientific literature has valid and reliable instruments that can be used in nursing care practice aimed at the evaluative, preventive and curative care of pressure injuries in pediatric and hebiatric patients.